Proteolytic cleavage of the voltage-gated Ca2+ channel α(2)δ subunit: structural and functional features - Andrade, Arturo (Blackwell Science, 2007)
By mediating depolarization-induced Ca(2+) influx high voltage-activated (HVA) Ca(2+) channels control a variety of cellular events. These heteromultimeric proteins are composed of an ion-conducting (α(1)) and three auxiliary (α(2)δ, β and γ) subunits. The α(2)δ subunit enhances the trafficking of the channel complex to the cell surface and increases channel open probability. To exert these effects, α(2)δ must undergo important post-translational modifications including a proteolytic cleavage that separates the extracellular α(2) from its transmembrane δ domain. After this proteolysis both domains remain linked by disulfide bonds. In spite of its central role in determining the final conformation of the fully mature α(2)δ almost nothing is known about the physiological implications of this structural modification. In the current report, by using site-directed mutagenesis, the proteolytic site of α(2)δ was mapped to amino acid residues Arg-941 and Val-946. Substitution of these residues renders the protein insensitive to proteolytic cleavage as evidenced by the lack of molecular weight shift upon treatment with a disulfide reducing agent. Interestingly, these mutations significantly decreased whole-cell patch clamp currents without affecting the voltage-dependence or kinetics of the channels, suggesting a reduction in the number of channels targeted to the plasma membrane.